Visuospatial short-term memory and dorsal visual gray matter volume. (April 2019) - Dimond, Dennis; Perry, Rebecca; Iaria, Giuseppe; Bray, Signe
Abstract: Visual short-term memory (VSTM) is an important cognitive capacity that varies across the healthy adult population and is affected in several neurodevelopmental disorders. It has been suggested that neuroanatomy places limits on this capacity through a map architecture that creates competition for cortical space. This suggestion has been supported by the finding that primary visual (V1) gray matter volume (GMV) is positively associated with VSTM capacity. However, evidence from neurodevelopmental disorders suggests that the dorsal visual stream is more broadly vulnerable and atypical volumes of other map-containing regions may therefore play a role. For example, Turner syndrome is associated with concomitantly reduced volume of the right intraparietal sulcus (IPS) and deficits in VSTM. As posterior IPS regions (IPS0-2) contain topographic maps, together this suggests that posterior IPS volumes may also associate with VSTM. In this study, we assessed VSTM using two tasks, as well as a composite score, and used voxel-based morphometry of T1-weighted magnetic resonance images to assess GMV in V1 and right IPS0-2 in 32 healthy young adults (16 female). For comparison with previous work, we also assessed associations between VSTM and voxel-wise GMV on a whole-brain basis. We found that total brain volume (TBV) significantly correlated with VSTM, and that correlations between VSTM and regional GMV were substantially reduced in strength when controlling for TBV. In our whole-brain analysis, we found that VSTM was associated with GMV of clusters centered around the right putamen and left Rolandic operculum, though only when TBV was not controlled for. Our results suggest that VSTM ability is unlikely to be accounted for by the volume of an individual cortical region, and may instead rely on distributed structural properties.